UJI DAYA HAMBAT EKSTRAK RIMPANG SEGAR KUNYIT PUTIH (Curcuma zedoaria, Berg) TERHADAP PERTUMBUHAN KUMAN GRAM POSITIF DAN GRAM NEGATIF IN VITRO - Bahar, Elizabeth (Universitas Andalas, 2009)
ABSTRACT Known as white turmeric crop of crop medicines anti cancer where this crop rimpang contain immeasurable chemical vitamin in the reality can pursue many of cancer cell. Though unegual germ cell its structure with cancer cell but process many of is same cell perform a replicace. Have been done/conducted by research of test sensitivity of extract of rimpang fresh of white turmeric in so many concentration 100%, 75%, 50% and 25% to growth of germ of Staphylococcus aureus, Salmonella typhii, Pseudomonas aeruginosa dan Escherichia coli of in vitro to know its sensitivity. Research of experiment by using factorial pattern in complete random device (RAL) with 5 restating. From result of research obtained by extract of rimpang fresh white tumeric in so many concentration not pursue growth of germ of Staphylococcus aureus, Salmonella typhi, Pseudomonas aeruginosa dan Escherichia coli. Its conclusion of extract of rimpang fresh of white turmeric non influence growth of Gram positive and Gram negative bacteria. Keywords: extract, fresh rimpang, white turmeric, germ